Efficacy of additional tissue sections for diminutive colorectal adenomas pathologically diagnosed as normal mucosa: a retrospective, cross-sectional study in Japan - Tsuyoshi Ishii; Toshihiro Nishizawa; Hidenobu Watanabe; Masaya Sano; Ai Fujimoto; Yoshiyuki Takahashi; Ryo Shimizu; Hirotoshi Ebinuma; Takahisa Matsuda; Osamu Toyoshima (Clinical Endoscopy)
Background/Aims Endoscopists occasionally encounter discrepancies between endoscopic and pathological diagnoses after colorectal polypectomies. This study aimed to evaluate the efficacy of additional sections for diagnostic discrepancies. Methods We examined polyps endoscopically diagnosed as adenomas or suspected adenomas that were resected and pathologically diagnosed as adenomas or normal mucosa. Adenomas pathologically diagnosed with initial sections were categorized as the “adenoma by initial section” group. Based on the re-diagnosis with additional sectioning, they were assigned to the “adenoma by additional section” or “normal mucosa by both sections” groups. Results In the initial pathological diagnosis of 993 lesions, 850 were diagnosed as adenomas and 143 as normal mucosa. Additional sections corrected the pathological diagnoses in 23.8% (34/143) of cases. The rate of high confidence was significantly higher in the “adenoma by additional section” group than in the “normal mucosa by both sections” group (64.7% vs. 38.5%, p<0.01). Lesions in the “adenoma by additional section” group were significantly smaller than those in the “adenoma by initial section” group (2.7 vs. 3.8 mm, p<0.05). Conclusions Diminutive adenomas can cause discrepancies between endoscopic and pathological diagnoses. Additional sections may help revise the pathological diagnoses, particularly for lesions with high confidence.